2005
DOI: 10.1159/000087796
|View full text |Cite
|
Sign up to set email alerts
|

Incidentally Detected Prostate Cancer in Cystoprostatectomy Specimens

Abstract: Objectives: Bladder and prostate cancers occur with increasing prevalence in the ageing population. Our study aims to quantify the incidence of prostate cancer in patients undergoing cystoprostatectomy for bladder cancer and assess the impact of that incidental prostate cancer on oncological outcome. Methods and Materials: We retrospectively reviewed the pathology reports of 128 men who underwent cystoprostatectomy for bladder cancer. Results: Twenty-three men (18%) were found to have incidental prostate cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 13 publications
2
14
0
3
Order By: Relevance
“…Unsuspected prostate cancer in radical cystoprosatectomy specimens were shown to generally involve small lesions localized within the prostate [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The present study also confirmed this finding; that is, incidentally detected prostate cancer was regarded as having more favorable characteristics in terms of serum PSA, pathological stage, Gleason score, perineural invasion and capsular penetration than clinically detected prostate cancer.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Unsuspected prostate cancer in radical cystoprosatectomy specimens were shown to generally involve small lesions localized within the prostate [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The present study also confirmed this finding; that is, incidentally detected prostate cancer was regarded as having more favorable characteristics in terms of serum PSA, pathological stage, Gleason score, perineural invasion and capsular penetration than clinically detected prostate cancer.…”
Section: Discussionsupporting
confidence: 81%
“…In this series, incidental prostate cancers were found in 12.3% of cystoprostatectomy specimens, which was remarkably low compared with those in previous studies from Western countries; that is, when the outcomes of 18 studies summarized in Table 3 were combined, the proportion of incidental prostate cancer in Western countries appeared to be 28.0% [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Considering the well-established finding that the incidence of latent prostate cancer in Japan is similar to that in Western countries [22], these outcomes suggest that different mechanisms are involved in the development of incidental and latent cancers in Japanese and Western men.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…As Delongchamps et al mentioned, in patients with concomitant prostate cancer, the poor survival rate was due to the majority of advanced bladder tumors and the outcome would be probably similar as the patients without coexisting prostate cancer [36]. Other authors also have found the same results [17], [37][38]. In this case, another oncological problem would focus on whether incidental significant prostate cancer could affect the cancer specific survival of these patients.…”
Section: Discussionmentioning
confidence: 66%